Ovarian remnant syndrome after laparoscopic ovariectomy in a cat - Properzi, R.; Boschi, P.; Leonardi, F. (Journal of the Hellenic Veterinary Medical Society, 2019)
The first case of accidental implantation of ovarian tissue at the port site after laparoscopic ovariectomy in a cat was described. A 2-year-old, spayed female, domestic cat showed recurrent behavioral oestrus signs (vocalization, increased playfulness, and lordosis) four months after laparoscopic ovariectomy. Abdominal ultrasound revealed bilateral endometrial hyperplasia and an inhomogeneous mass attached to the abdominal wall at the port site of previous laparoscopic ovariectomy. Ovarian remnant syndrome was supposed. Diagnostic laparoscopy confirmed the presence of a mass that was 2 cm in diameter and macroscopically similar to ovarian tissue. Laparoscopy was converted to laparotomy to remove the abnormal tissue and the uterus. Histopathological findings showed follicles of various maturation stages in the mass, and confirmed endometrial hyperplasia. Histology underscored that ovarian remnant tissue resumed function. No clinical signs consistent with ovarian remnant syndrome were reported six months after removal of the abnormal tissue. In conclusion, removal of the ovaries through the laparoscopic port site may cause fortuitous ovarian tissue implantation at the abdominal wall in the cat.